2002
DOI: 10.1256/003590002320603566
|View full text |Cite
|
Sign up to set email alerts
|

On the thermodynamics of the oceanic general circulation: Irreversible transition to a state with higher rate of entropy production

Abstract: SUMMARYThe mechanism of transitions among multiple steady states of thermohaline circulation is investigated from a thermodynamic viewpoint. An oceanic general-circulation model is used to obtain the multiple steady states under the same set of wind forcing and mixed boundary conditions, and the rate of entropy production is calculated during time integration. Three states with northern sinking and four states with southern sinking are shown to exist in the model by perturbing the high-latitude salinity. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…Furthermore, entropy production provides a unifying perspective of seemingly different processes in the climate system (energy vs. water vs. carbon fluxes) and it is well suited in that it provides a clear reference point defined by states of maximum entropy production (e.g. Paltridge, 1978;Grassl, 1981;Ozawa and Ohmura, 1997;Shimokawa and Ozawa, 2002;Lorenz et al, 2001;Ozawa et al, 2003;Kleidon et al, 2003Kleidon et al, , 2006Kleidon and Fraedrich, 2005). This thermodynamic interpretation of climate sensitivity would seem worthy of further development and applications to other topics related to global climatic change.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, entropy production provides a unifying perspective of seemingly different processes in the climate system (energy vs. water vs. carbon fluxes) and it is well suited in that it provides a clear reference point defined by states of maximum entropy production (e.g. Paltridge, 1978;Grassl, 1981;Ozawa and Ohmura, 1997;Shimokawa and Ozawa, 2002;Lorenz et al, 2001;Ozawa et al, 2003;Kleidon et al, 2003Kleidon et al, , 2006Kleidon and Fraedrich, 2005). This thermodynamic interpretation of climate sensitivity would seem worthy of further development and applications to other topics related to global climatic change.…”
Section: Discussionmentioning
confidence: 99%
“…One of the tenets of modern non-equilibrium thermodynamics is that systems not constrained to be at steady state will evolve to that state which tends to maximize entropy production. Such a principle has proved invaluable in explaining aspects of the Earth's climate (Paltridge 1975(Paltridge , 1978(Paltridge , 2001, the oceanic general circulation (Shimokawa & Ozawa 2002), and the fundamental mechanical, hydraulic and chemical behaviour of solids (Ziegler 1983a,b;Coussy 1995Coussy , 2004Houlsby & Puzrin 2006). The principle has a basis in statistical mechanics (Dewar 2005) where it has been shown that a state of maximum entropy production rate is the most probable state for large systems not at equilibrium and not constrained to be at steady state.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to keep in mind that (contrary to what is claimed in [2]) the constitutive equations derived from the above Lagrangian are only compatible with (18) and (23) when ij F ij ∂A ij,kl ∂F lm = 0. It is clear that this restriction does not hold in the non-linear regime of our model with constitutive equations (11).…”
Section: Ziegler's and Linear Response Maxepmentioning
confidence: 86%